Immunomodulatory effects of herbal plants plus melatonin on human blood phagocytes - Eduardo Luzia França,; Joanna Conde Maynié,; Valéria Conde Correa,; Uender Correia Rodrigues Pereira,; Claudemir Batalini,; Carlos Kusano Bucalen Ferrari,; Adenilda Cristina Honorio-França, (International Journal of Phytomedicine, 2010)
It has been shown a mixture of seven herbal plants was able to trigger cell oxidative mechanism and subsequently inducing cellular activation. Moreover, melatonin hormone has also been shown to perform different actions on the cellular oxidative metabolism. It is possible that the herbal mixture associated with melatonin can activate phagocytes, improving microbicidal activity and further ameliorating resistence to the infections. The aim of this work was to verify in vitro immunomodulatory effects of melatonin and a medicinal plants mixture on blood mononuclear phagocytes (MN). We collected 40 blood samples from normal individuals to obtain the phagocytes. The MN phagocytes were separated by Ficoll-Paque gradient. Preparation of plant extract to obtain the herbal mixture was carried through the process of maceration followed by distillation. Phagocytosis and microbicidal activity of blood phagocytes, treated or not with exogenous superoxide dismutase (SOD), against enterophathogenic Escherichia coli (EPEC) were evaluated by acridine orange method. The herbal mixture and/or melatonin were added to the cell suspensions as immunomodulators. We observed increased phagocytosis and microbicidal activities by blood MN phagocytes in the presence of melatonin or the herbal mixture. The association of both potentiated the functional activity of blood MN phagocytes. Phagocytes previously treated by exogenous SOD had decreased microbicidal activity independently of immunomodulators. These data suggest that the herbal mixture is a potent immunostimulatory agent, and that the interaction between plant and hormones may represent an alternative mechanism of defense against infection, especially in immunosuppressed patients.